Distinct Residential and Infiltrated Macrophage Populations and Their Phagocytic Function in Mild and Severe Neonatal Hypoxic-Ischemic Brain Damage - Min, Yingjun; Yan, Lin; Wang, Qian; Wang, Fang; Hua, Hairong; Yuan, Yun; Jin, Huiyan; Zhang, Ming; Zhao, Yaling; Yang, Jianzhong; Jiang, Xiangning; Yang, Yuan; et al. (Frontiers in Cellular Neuroscience, 2020)
Neonatal brain injury, especially severe injury induced by hypoxia-ischemia (HI), causes mortality and long-term neurological impairments. Our previous study demonstrated activation of CD11b+ myeloid cells, including residential microglial cells (MCs) and infiltrating monocyte-derived macrophages (MDMs) in a murine model of hypoxic-ischemic brain damage (HIBD), with unknown functions. Here, we study the differences in the phagocytic function of MCs and MDMs to clarify their potential roles after HIBD. In this study, HI was induced in 9-11-day postnatal mice. On days 1 and 3 after injury, pathological and neurobehavioral tests were performed to categorize the brain damage as mild or severe. Flow cytometry was applied to quantify the dynamic change in the numbers of MCs and MDMs according to the relative expression level of CD45 in CD11b+ cells. CX3CR1GFPCCR2RFP double-transformed mice were used to identify MCs and MDMs in the brain parenchyma after HIBD. LAMP1, TLR2, CD36 and TGF-β expression levels were measured to assess the underlying function of phagocytes and neuroprotective factors in these cells. The FITC-dextran 40 phagocytosis assay was applied to examine the change in phagocytic function under oxygen-glucose deprivation (OGD) in vitro. We found neonatal HI induced different degree of brain damage: mild or severe injury. Compared with mildly injured animals, mice with severe injury had lower weight, worse neurobehavioral scores, and abnormal brain morphology. In severely injured brain, CD11b+ cells remarkably increased, including an increase in the MDM population and a decrease in the MC population. Furthermore, MDM infiltration into the brain parenchyma was evident in CX3CR1GFPCCR2RFP double-transformed mice. Mild and severe brain injury caused different phagocytosis-related responses and neuroprotective functions of MDMs and MCs at 1 and 3 d following HI. Phagocytic function was activated in BV2 cells but downregulated in Raw264.7 cells under OGD in vitro. These observations indicate that neonatal HI induced different degrees of brain injury. The proportion of infiltrated macrophage MDMs increased and were recruited into the injured brain parenchyma in severe brain injury. The resident macrophage MCs proportion decreased and maintained activated phagocytic function in both mild and severe brain injury, and restored neuroprotective function in severe brain injury.